2002
DOI: 10.1104/pp.008334
|View full text |Cite
|
Sign up to set email alerts
|

Alternate Energy-Dependent Pathways for the Vacuolar Uptake of Glucose and Glutathione Conjugates

Abstract: Through the development and application of a liquid chromatography-mass spectrometry-based procedure for measuring the transport of complex organic molecules by vacuolar membrane vesicles in vitro, it is shown that the mechanism of uptake of sulfonylurea herbicides is determined by the ligand, glucose, or glutathione, to which the herbicide is conjugated. ATP-dependent accumulation of glucosylated chlorsulfuron by vacuolar membrane vesicles purified from red beet (Beta vulgaris) storage root approximates Micha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
67
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 45 publications
2
67
0
1
Order By: Relevance
“…Modification of flavonoids and other compounds by processes such as glycosylation and acylation is often a necessary prerequisite for their transport into the vacuole by MATE or ABC transporters (Klein et al, 1996;Bartholomew et al, 2002;Marinova et al, 2007;Gomez et al, 2009), and flavonoid aglycones are generally not suitable substrates for MATE transporters. Arabidopsis TT12 transports Cy3G but not C3G, flavonoid aglycones, or flavonol glucosides, such as quercetin-3-O-glucoside (Marinova et al, 2007).…”
Section: Tt2 Induces Flavonoid Transporters In Medicago Hairy Rootsmentioning
confidence: 99%
“…Modification of flavonoids and other compounds by processes such as glycosylation and acylation is often a necessary prerequisite for their transport into the vacuole by MATE or ABC transporters (Klein et al, 1996;Bartholomew et al, 2002;Marinova et al, 2007;Gomez et al, 2009), and flavonoid aglycones are generally not suitable substrates for MATE transporters. Arabidopsis TT12 transports Cy3G but not C3G, flavonoid aglycones, or flavonol glucosides, such as quercetin-3-O-glucoside (Marinova et al, 2007).…”
Section: Tt2 Induces Flavonoid Transporters In Medicago Hairy Rootsmentioning
confidence: 99%
“…Virtually all of the compound (.98%) accumulated in the vacuole as two Glc conjugates, a phenolic glucoside and a Glc ester, which both contained a single Glc molecule attached to the aromatic hydroxyl or carboxyl group of pHBA by a 1-O-b-D linkage. Glc conjugation, which takes place in the cytosol via distinct UDPglucosyltransferases , is required for vacuolar uptake, and recent studies have shown that the pHBA phenolic glucoside and Glc ester are transported by separate carriers that have different mechanisms (Bartholomew et al, 2002). The highest leaf content of pHBA Glc conjugates in nucleartransformed tobacco (Nicotiana tabacum) plants was 0.52% dry weight, which is equivalent to 0.24% free pHBA after correcting for the mass of the attached Glc residue.…”
mentioning
confidence: 99%
“…This implies that further research is still required to clarify their precise relationships because the glutathione conjugation of xeonobiotics is well known to be a prerequisite reaction for their efficient transfer to the vacuole as it is described with glycosylation. 27) The major secondary metabolite observed in duckweed exposed to I-VI was the glycoside conjugates. Glycoside conjugation is known to be one of the most common transformations for chemicals having the amino, hydroxy or carboxy group in plants.…”
Section: Discussionmentioning
confidence: 99%